PENGARUH KINERJA KARYAWAN SALON KECANTIKAN TERHADAP KEPUASAN PELANGGAN DI KECAMATAN PADANG TIMUR - Ayuning, Geby , Denada; Hayatunnufus, Hayatunnufus; Astuti, Murni (Journal of Home Economics and Tourism, 2017)
This research is based on the problems shows that the low employee performance in fulfilling the customer satisfaction, it is seen from the lack of knowledge and ability of employees to perform in doing his job. This research is aims to show the given influence by the beauty salon employee performance on customer satisfaction in the District of East Padang. This research is descriptive quantitative research. The population in this research was the customers beauty salon visited in the beauty salon in the District of East Padang. The technique of sampling in research is accidental sampling and the sample was obtained as many as 57 people. The collection of data from respondents was conducted through a questionnaire. Before being used of data collection first tested the validity and reliability test items to determine the feasibility of the items that will be proposed in the research. Then the collected data testing requirements analysis using analysis of normality and linearity test, simple linear regression test, and test the coefficient of determination to calculate the influence of employee performance variables (X) on a beauty salon customer satisfaction variable (Y). Based on the analysis of data obtained the result that the employee's performance of the level of achievement acquired beauty salon respondents of total 82.72% with a good category and for the satisfaction of customers acquired of total 72.36% with a normal category. From the results of analysis of the simple linear regression test both significant influential variable with the correlation of 0.637. Ha hypothesis explains that the influence a positive between beauty salon employee performance on customer satisfaction is received with trust level of total 95%. Then seen from the results of the analysis of the coefficient of determination can be known the magnitude of the contribution of employee performance on beauty salon customer satisfaction of total 40.58% Keywords: Employee Performance, customer satisfaction, Beauty Salon